The Relationship Between Exclusive Breastfeeding With Stunting Incidence In 24-60 Month Toddlers - Siswati, Suci; Sujiyatini, Sujiyatini; Kristijono, Anton (Jurnal Kesehatan Ibu dan Anak, 2023)
Improving maternal and child health is one of the indicators for minimum service standards, where reducing stunting is one of the targets. Stunting is a lack of energy in the long term, one of the contributing factors is breastfeeding. Exclusive breastfeeding is important in the first 1000 days of live birth. Objective: To determine the relationship between exclusive breastfeeding with incidents of stunting at the Nasik Strait Health Center, Belitung Regency. This study used a cross-sectional design. The study population was mothers of toddlers aged 24 months – 60 months in the Selat Nasik Health Center area. The proportional stratified random technique was used with inclusion and exclusion criteria totaling 63 people. Collecting data using a data collection questionnaire. Data analysis used univariate and bivariate analysis (who squares). The results of the analysis show that only 58.7% of mothers giving exclusive breastfeeding at the Selat Nasik Health Center are only 58.7%. Bivariate test results show that there is no relationship between exclusive breastfeeding and the incidence of stunting in toddlers 24 months – 60 months.p-value = 0,952 (>0,05). Conclusion: Mothers of infants who breastfeed exclusively and mothers who do not breastfeed exclusively are still at risk of having infants stunting, so mothers need to pay attention to other factors that cause it stunting.